Technology and Skills in Singapore - Chng, Meng Kng; Low, Linda; Tay, Boon Nga (ISEAS Publishing, 1986)
This is one of four country papers resulting from the ASEAN Regional Studies Programme. Relying on primary data collected through field surveys and various materials including those from official sources not readily available in published form, the papers deal comprehensively with the problems related to the task of acquiring technology from developed countries - specifically Japan. In addition to the identification and examination of problems and issues common to the ASEAN countries, each paper gives a lucid account of special factors related to the state of technology transfer skills enhancement in the particular country concerned